Inhibiting Multidrug Resistance with Transferrin-Targeted Polymersomes through Optimization of Ligand Density - Yi, Shui Ling (Langmuir : the ACS journal of surfaces and colloids, 2023)
Transferrin-conjugated polymersomes, transferrin-biotin/avidin/biotin-Pluronic F127-poly(lactic acid) (Tf-F127-PLA), were successfully prepared through a biotin-avidin bridging technique to study their ability to inhibit multidrug resistance of cancer cells. Hydrophilic doxorubicin (DOX) was selected as the model drug to be loaded into Tf-F127-PLA polymersomes. DOX loaded in Tf-F127-PLA polymersomes was released fast initially, followed by a slow release. The effect of the transferrin ligand density of Tf-F127-PLA/DOX polymersomes on their targeting properties was studied by both cytotoxicity and cellular uptake assays against A549 lung cancer cells. It was shown that Tf-F127-PLA/DOX polymersomes had better targeting ability than nontargeted drug-loaded polymersomes. Furthermore, Tf-F127-PLA/DOX polymersomes with 2% Tf molar content have more effective antitumor activity and a higher cellular uptake than those with 4 and 5% Tf molar content. 2% Tf-F127-PLA/DOX polymersomes also exhibited better anticancer ability in multidrug resistant cancer cells A549/ADR than nontargeted PLA-F127-PLA/DOX polymersomes. It was further proved that the endocytosis of polymersomes by A549/ADR cells was an energy-dependent endocytosis process, which was related to clathrin, macrocytosis, and caveolin. Also, the endocytosis of Tf-F127-PLA/DOX polymersomes was proven to be mediated by the transferrin receptor